Multilayer structure and packaging material using the same
Patent Information
- Application Number
- JP2023124312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0009】 本発明の多層構造体及びそれを用いた包装材料は、ガスバリア性、ヒートシール性、落下破袋耐性及びリサイクル性に優れる。
Smart Images

Figure 2025020747000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer structure having excellent gas barrier properties, resistance to bag breakage due to dropping, and recyclability, and a packaging material using the same. [Background technology]
[0002] Packaging materials for long-term food storage are often required to have gas barrier properties, including oxygen barrier properties. By using packaging materials with high gas barrier properties, it is possible to suppress oxidative deterioration of food caused by oxygen intrusion and the proliferation of microorganisms. Metal foils such as aluminum, metal deposition layers, and inorganic deposition layers such as silicon oxide and aluminum oxide are widely used as layers that improve gas barrier properties. On the other hand, resin layers with gas barrier properties such as vinyl alcohol polymers and polyvinylidene chloride are also widely used. Vinyl alcohol polymers have the characteristic of exhibiting gas barrier properties by crystallizing and densifying due to hydrogen bonding between hydroxyl groups in the molecules. Among them, ethylene-vinyl alcohol copolymers (hereinafter sometimes abbreviated as "EVOH") are suitable for melt molding due to their excellent thermal stability, and with the development of coextrusion technology, multilayer structures with an EVOH layer as an intermediate layer are widely used as gas barrier packaging materials.
[0003] In recent years, environmental and waste problems have led to a worldwide demand for post-consumer recycling (hereinafter sometimes abbreviated as recycling), which involves collecting and recycling packaging materials consumed in the market. In recycling, the collected packaging materials are generally cut, separated and washed as necessary, and then melt-mixed using an extruder. In this regard, packaging materials are required to be composed of a single material as much as possible (mono-materialization), which allows for the production of high-purity, high-quality recycled raw materials. For example, gas-barrier packaging materials having a polyamide layer and an EVOH layer are commonly used because of their excellent mechanical strength, but the polyamide resin and EVOH react chemically to generate particles, which can reduce recyclability. Taking these issues into consideration, it is necessary to realize mono-materialization in order to provide gas-barrier packaging materials with excellent recyclability while maintaining their gas barrier properties and mechanical strength.
[0004] Patent Document 1 describes that a multilayer structure having a hard layer with a puncture strength of 40 N / mm or more and 150 N / mm or less and (1) a resin composition layer having EVOH with a melting point of 170°C or more and EVOH with a melting point of less than 170°C, or (2) a resin composition layer having modified EVOH containing a modifying group with a specific primary hydroxyl group, has excellent mechanical strength and thermoformability despite not having a polyamide layer, and when the recovered material is melt-molded, the generation of bumps due to deterioration (gelation) of the resin is suppressed, and the structure also has excellent recyclability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 071513 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the multilayer structure described in Patent Document 1, the melting points of both outermost surfaces are the same or close to each other, and there are problems with processability, especially heat sealing, when producing packaging materials such as pouches and filling them with food, etc. Furthermore, when the multilayer structure is laminated with a biaxially oriented polypropylene film for the purpose of improving processability, while the processability is improved, there are cases in which resistance to bag breakage due to dropping, particularly at low temperatures, is insufficient.
[0007] The present invention has been made to solve the above problems, and has an object to provide a multilayer structure excellent in gas barrier property, heat sealability, drop-breakage resistance, and recyclability, and a packaging material using the same. [Means for solving the problem]
[0008] According to the present invention, the above object is [1] A film having a sealant layer (X) and a base layer (Y), in which the sealant layer (X) comprises a barrier layer (A) containing, as a main component, an ethylene-vinyl alcohol copolymer (a) (hereinafter sometimes abbreviated as "EVOH (a)") having an ethylene unit content of 20 to 50 mol% and a saponification degree of 90 mol% or more, an adhesive layer (B) containing, as a main component, an adhesive resin (b), and a film having a density of 0.880 to 0.930 g / cm 3 a base layer (Y) containing as a main component polypropylene (y) having a melting point of 140°C or more as measured by a differential scanning calorimeter (DSC), and having an elastic modulus of 1000 MPa or less in both the machine direction (MD) and the width direction (TD) under conditions of 23°C and 50% RH; and a heat-sealable layer (C) of a sealant layer (X) on the outermost surface; [2] The puncture strength S measured according to JIS Z1707:2019 at 23°C and 50% RH, and the puncture strength S of the sealant layer (X) measured according to JIS Z1707:2019 at 23°C and 50% RH X Difference with (SS X ) is 3.0 N or more; [3] The multilayer structure according to [2], wherein the puncture strength S is 9N or more; [4] The multilayer structure of any one of [1] to [3], wherein the haze of the base layer (Y) measured in accordance with JIS K 7136:2000 is 35% or less; [5] The multilayer structure of any one of [1] to [4], wherein the sealant layer (X) and the base layer (Y) are laminated via an adhesive layer (Z), and the adhesive layer (Z) has a thickness of 2 to 7 μm; [6] The multilayer structure of any of [1] to [5], wherein the ethylene-α-olefin copolymer resin (c) is a linear low-density polyethylene copolymerized with ethylene and an α-olefin having 6 or more carbon atoms; [7] A multilayer structure according to any one of [1] to [6], wherein the barrier layer (A) contains a boron compound in an amount of 50 to 400 ppm in terms of elemental boron; [8] The multilayer structure of any one of [1] to [7], wherein the ethylene unit content of EVOH (a) is 22 mol% or more and 28 mol% or less; [9] The multilayer structure of any one of [1] to [8], wherein the thickness of the barrier layer (A) is 5 μm or less;
[10] The oxygen transmission rate measured according to the method described in JIS K 7126-2:2006 under conditions of 20°C and 65% RH is 5cc / (m 2 A multilayer structure of any one of [1] to [9], in which the thermal conductivity is less than 100% (day·atm);
[11] The water vapor transmission rate measured according to the method described in JIS K 7129-2:2019 at 40°C and 90% RH is 3g / (m 2 A multilayer structure of any one of [1] to
[10] , wherein the drying time is 1-4 days or less;
[12] A packaging material comprising any one of the multilayer structures of [1] to
[11] ; This is achieved by providing Effect of the Invention
[0009] The multilayer structure of the present invention and the packaging material using the same are excellent in gas barrier property, heat sealability, resistance to bag breakage due to dropping, and recyclability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described. In the following description, specific materials (compounds, etc.) that exhibit specific functions may be exemplified, but the present invention is not limited to the embodiment using such materials. Furthermore, the exemplified materials may be used alone or in combination, unless otherwise specified.
[0011] The multilayer structure of the present invention has a sealant layer (X) and a base layer (Y), in which the sealant layer (X) comprises a barrier layer (A) containing, as a main component, EVOH (a) having an ethylene unit content of 20 to 50 mol% and a saponification degree of 90 mol% or more, an adhesive layer (B) containing, as a main component, an adhesive resin (b), and a cellulose acylate having a density of 0.880 to 0.930 g / cm. 3 The heat-sealing layer (C) mainly contains an ethylene-α-olefin copolymer resin (c) as a base material layer (Y), which mainly contains polypropylene (y) having a melting point of 140° C. or more as measured by a differential scanning calorimeter (DSC), and has a modulus of elasticity in both the machine direction and the width direction under conditions of 23° C. and 50% RH of 1000 MPa or less, and has the heat-sealing layer (C) of the sealant layer (X) on the outermost surface. Here, "mainly contains" means that it contains more than 50% by mass, but it is preferable that it contains 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and it may be an embodiment that it contains 95% by mass or more, 97% by mass or more, or 99% by mass or more. By providing the barrier layer (A), the multilayer structure of the present invention tends to be able to improve gas barrier properties while maintaining recyclability. In addition, by providing the adhesive layer (B), it tends to be able to improve mechanical strength including drop-breakage resistance and recyclability. The main component of the thermal adhesive layer (C) has a density of 0.880 to 0.930 g / cm 3By using the ethylene-α-olefin copolymer resin (c) of the present invention, excellent mechanical strength including drop-breakage resistance tends to be realized while maintaining heat sealability. Furthermore, by using the base layer (Y) of the multilayer structure of the present invention, which contains polypropylene (y) having a melting point of 140° C. or more as measured by a differential scanning calorimeter (DSC) as a main component and both of the elastic modulus in the machine direction and the width direction under conditions of 23° C. and 50% RH are 1000 MPa or less, the heat sealability is improved and drop-breakage resistance, particularly drop-breakage resistance under low temperature conditions, tends to be improved. In addition, the drop-breakage resistance in this specification can be evaluated by the number of tests until water leakage occurs when a bag made using the multilayer structure of the present invention is filled with contents and dropped from a certain height, and can be specifically evaluated by the method described in the Examples. In addition, when it is expressed as drop-breakage resistance, it basically means drop-breakage resistance at room temperature and low temperature. In addition, the recyclability in this specification can be evaluated by the occurrence of bumps in a melt-molded product obtained by melt-kneading a crushed product of the multilayer structure, and can be specifically evaluated by the method described in the Examples. In this specification, "barrier properties" refers to oxygen barrier properties and water vapor barrier properties, and "gas barrier properties" refers to oxygen barrier properties.
[0012] In this specification, "ppm" refers to the content based on mass (ppm by mass). The term "surface (or surface layer)" in a multilayer film or multilayer structure does not mean to distinguish between the front and back, but refers to the exposed surface. In other words, a multilayer film or multilayer structure has two surfaces. Similarly, a multilayer film or multilayer structure has two outermost surfaces. In this specification, "consists essentially of" means that optional components may be contained within a range that does not affect the effects of the present invention, and "consists only of" means that optional components other than impurities that are inevitably contained are excluded.
[0013] <Barrier layer (A)> The multilayer structure of the present invention has a barrier layer (A) containing EVOH (a) as a main component. Since EVOH (a) has excellent gas barrier properties, a multilayer structure having a layer containing EVOH (a) as a main component is preferably used as a packaging material with excellent content preservation properties. In addition, since EVOH (a) can be easily melt-mixed with polyolefin resins, a packaging material with excellent recyclability can be provided.
[0014] EVOH (a) is usually obtained by saponifying an ethylene-vinyl ester copolymer obtained by polymerizing ethylene and a vinyl ester. A representative vinyl ester is vinyl acetate, but other fatty acid vinyl esters (vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, vinyl versatate, etc.) can also be used.
[0015] The ethylene unit content of EVOH(a) is 20 to 50 mol%. When the ethylene unit content is 20 mol% or more, the melt moldability of EVOH(a) and the pulverized product of the multilayer structure containing EVOH(a) is improved. The ethylene unit content is preferably 21 mol% or more, more preferably 22 mol% or more, and may be 25 mol% or more. On the other hand, when the ethylene unit content is 50 mol% or less, the gas barrier property of the multilayer structure of the present invention is improved. The ethylene unit content is preferably 46 mol% or less, more preferably 39 mol% or less, even more preferably 33 mol% or less, particularly preferably 28 mol% or less, and may be 26 mol% or less. In addition, the saponification degree of EVOH(a) is 90 mol% or more. The saponification degree means the ratio of the number of vinyl alcohol units to the total number of vinyl alcohol units and vinyl ester units in EVOH(a). When the saponification degree is 90 mol% or more, the gas barrier property of the multilayer structure of the present invention is improved. The saponification degree is preferably 95 mol% or more, more preferably 99 mol% or more, and even more preferably 99.9 mol% or more. The saponification degree may be 100 mol% or less. The ethylene unit content and saponification degree of EVOH (a) are as follows: 1 It can be determined by H-NMR measurement.
[0016] EVOH (a) may be a mixture of two or more EVOHs having different ethylene unit contents. In this case, the difference in ethylene unit content between the EVOHs having the most different ethylene unit contents is preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 20 mol% or less, and may be 3 mol% or more. Similarly, EVOH (a) may be a mixture of two or more EVOHs having different saponification degrees. In this case, the difference in saponification degree between the EVOHs having the most different ethylene unit contents is preferably 7 mol% or less, more preferably 5 mol% or less, and may be 0.5 mol% or more. When it is desired to achieve both thermoformability and gas barrier property at a higher level, it is preferable to mix EVOH (a1) having an ethylene unit content of 22 mol% or more and less than 34 mol% and a degree of saponification of 99 mol% or more with EVOH (a2) having an ethylene unit content of 34 mol% or more and less than 50 mol% and a degree of saponification of 99 mol% or more in a blending mass ratio (a1 / a2) of 60 / 40 to 90 / 10 and use the mixture as EVOH (a).
[0017] EVOH (a) may contain other monomer units other than ethylene, vinyl ester and vinyl alcohol, so long as the effects of the present invention are not impaired. In particular, by introducing a modified group containing a primary hydroxyl group having a specific structure, the gas barrier properties and moldability of EVOH (a) may be compatible at a high level. The content of other monomer units is preferably 10 mol% or less, more preferably 5 mol% or less, even more preferably 1 mol% or less, and particularly preferably substantially not contained. Examples of such other monomers include alkenes such as propylene, butylene, pentene, and hexene; 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl -1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, 5,6-diacyloxy ester group-containing alkenes or saponification products thereof, such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, or other unsaturated acids or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids or salts thereof, such as vinyl sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl silane compounds such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxy-ethoxy) silane, and γ-methacryloxypropyl methoxy silane; alkyl vinyl ethers, vinyl ketones, N-vinyl pyrrolidone, vinyl chloride, and vinylidene chloride.
[0018] EVOH (a) may be modified as necessary by urethanization, acetalization, cyanoethylation, oxyalkylenation, etc. Oxyalkylenation can be carried out using an epoxy compound, such as epoxyethane (ethylene oxide), epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, 3-methyl-1,2-epoxybutane, 1,2-epoxypentane, 3-methyl-1,2-epoxypentane, 1,2-epoxyhexane, 2,3-epoxyhexane, 3,4-epoxyhexane, 3-methyl-1,2-epoxyhexane, 3-methyl-1,2-epoxyheptane, 4-methyl-1,2-epoxyheptane, 1, Examples of such epoxy alkanols include 2-epoxyoctane, 2,3-epoxyoctane, 1,2-epoxynonane, 2,3-epoxynonane, 1,2-epoxydecane, 1,2-epoxydodecane, epoxyethylbenzene, 1-phenyl-1,2-propane, 3-phenyl-1,2-epoxypropane, various alkyl glycidyl ethers, various alkylene glycol monoglycidyl ethers, various alkenyl glycidyl ethers, various epoxy alkanols such as glycidol, various epoxy cycloalkanes, and various epoxy cycloalkenes. Among these, 1,2-epoxybutane, 2,3-epoxybutane, epoxypropane, epoxyethane, or glycidol is preferred, and epoxypropane or glycidol is more preferred.
[0019] The MFR (190°C, under a load of 2.16 kg) of EVOH(a) measured in accordance with JIS K7210(2014) is preferably 0.2 to 20 g / 10 min. The MFR of EVOH(a) is more preferably 0.5 g / 10 min or more, and even more preferably 0.8 g / 10 min or more. On the other hand, the MFR of EVOH(a) is more preferably 15 g / 10 min or less, even more preferably 10 g / 10 min or less, even more preferably 5 g / 10 min or less, and particularly preferably 3 g / 10 min or less. When the MFR of EVOH(a) is within the above range, the melt moldability of the pulverized product of EVOH(a) and the multilayer structure containing EVOH(a) (the multilayer structure of the present invention) is improved.
[0020] The barrier layer (A) may contain other components other than EVOH (a) as long as the effects of the present invention are not impaired. Examples of other components include alkali metal ions, polyvalent metal ions, carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, UV absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, bulking agents, pigments, dyes, processing aids, flame retardants, and antifogging agents. The content of other components in the barrier layer (A) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.
[0021] The barrier layer (A) preferably contains 10 to 400 ppm of alkali metal ions. The lower limit of the content of alkali metal ions is more preferably 100 ppm, and further preferably 150 ppm. On the other hand, the upper limit of the content of alkali metal ions is more preferably 350 ppm, and may be 250 ppm. When the content of alkali metal ions is 10 ppm or more, the interlayer adhesion in the multilayer structure of the present invention including the layer obtained by molding EVOH (a) is good. On the other hand, when the content of alkali metal ions is 400 ppm or less, coloration tends to be suppressed. In addition, by controlling the content ratio of alkali metal ions and carboxylic acid described later, melt moldability and coloration resistance can be further improved.
[0022] Examples of alkali metal ions include lithium, sodium, potassium, rubidium, and cesium ions, but sodium or potassium ions are preferred from the viewpoint of industrial availability. In particular, by using sodium ions, it may be possible to achieve high levels of both hue and interlayer adhesion with the adhesive layer. These may be used alone or in combination of two or more.
[0023] Examples of alkali metal salts that provide alkali metal ions include aliphatic carboxylates, aromatic carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes of alkali metals such as sodium and potassium. Among these, at least one selected from the group consisting of sodium acetate, potassium acetate, sodium phosphate, and potassium phosphate is more preferred from the viewpoint of easy availability.
[0024] The barrier layer (A) preferably contains 10 to 200 ppm of at least one polyvalent metal ion selected from the group consisting of magnesium ions, calcium ions, and zinc ions. By containing a certain amount of polyvalent metal ions, thickening, gelation, and resin adhesion to the screw are suppressed when EVOH (a) and the pulverized product of the multilayer structure containing EVOH (a) are melt-molded. The barrier layer (A) more preferably contains magnesium ions or calcium ions as the polyvalent metal ions, and further preferably contains magnesium ions. In addition, it is preferable to contain the polyvalent metal ions as carboxylates. The carboxylic acid in this case may be either an aliphatic carboxylic acid or an aromatic carboxylic acid, but an aliphatic carboxylic acid is preferable. Examples of the aliphatic carboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, lauric acid, stearic acid, myristic acid, behenic acid, and montanic acid, and higher fatty acids having 10 to 25 carbon atoms are more preferable. In addition, from the viewpoint of suppressing coloration during melt molding, it is also preferable to contain the polyvalent metal ions as salts of polyvalent carboxylic acids described later.
[0025] The content of polyvalent metal ions in the barrier layer (A) is preferably 10 to 200 ppm in terms of metal atoms. When the content is 10 ppm or more, the viscosity stability of EVOH (a) and the ground product of the multilayer structure containing EVOH (a) is improved, and gelation of the resin and adhesion of the resin to the extruder screw are suppressed. The lower limit of the content of polyvalent metal ions is more preferably 20 ppm. On the other hand, when the content of polyvalent metal ions is 200 ppm or less, excessive decomposition of the ground product of the multilayer structure containing EVOH (a) is suppressed, and the color of the recovered composition is improved. The upper limit of the content of polyvalent metal ions is more preferably 160 ppm, and even more preferably 120 ppm.
[0026] The barrier layer (A) preferably further contains a boron compound. The lower limit of the content of the boron compound is preferably 50 ppm, more preferably 100 ppm, in terms of boron element. On the other hand, the upper limit of the content of the boron compound is preferably 400 ppm, more preferably 300 ppm, in terms of boron element. By containing the boron compound within this range, the mechanical properties of the multilayer structure may be improved. Furthermore, the thermal stability of the EVOH (a) and the pulverized product of the multilayer structure during melt molding may be improved, and the occurrence of gels and bumps may be suppressed. Furthermore, the drawdown resistance and the neck-in resistance during film formation may be improved. It is presumed that these effects are due to the occurrence of a chelate interaction between the EVOH (a) and the boron compound.
[0027] Examples of boron compounds include boric acid, boric acid esters, borate salts, and boron hydrides.Specific examples include boric acids such as orthoboric acid (H3BO3), metaboric acid, and tetraboric acid; boric acid esters such as trimethyl borate and triethyl borate; alkali metal salts or alkaline earth metal salts of the boric acid, and borate salts such as borax.Of these, orthoboric acid is preferred.
[0028] The barrier layer (A) preferably contains a carboxylic acid. The lower limit of the content of the carboxylic acid is preferably 50 ppm, more preferably 100 ppm. On the other hand, the upper limit of the content of the carboxylic acid is preferably 400 ppm, more preferably 350 ppm. When the content of the carboxylic acid is within the above range, the deterioration of the hue tends to be suppressed. The content of the carboxylic acid is obtained by extracting 10 g of the resin composition constituting the barrier layer (A) with 50 ml of pure water at 95 ° C for 8 hours, and then titrating the obtained extract. Note that the content of the carboxylic acid in the resin composition does not take into account the carboxylic acid present as a salt in the extract. In addition, when the resin composition contains acidic compounds other than the carboxylic acid, the content of the carboxylic acid in the resin composition can be obtained by subtracting the contribution of these acidic compounds from the measured value by titration.
[0029] The pKa of the carboxylic acid is preferably 3.5 to 5.5. When the pKa of the carboxylic acid is within the above range, the pH buffering ability in the weak acid range is increased, the melt moldability is further improved, and the coloring effect due to acidic or basic substances can be further reduced.
[0030] The carboxylic acid may be a monobasic carboxylic acid. These may be used alone or in combination of two or more. The monobasic carboxylic acid is a compound having one carboxy group in the molecule. Examples of monobasic carboxylic acids having a pKa in the range of 3.5 to 5.5 include, but are not limited to, formic acid (pKa=3.77), acetic acid (pKa=4.76), propionic acid (pKa=4.85), and acrylic acid (pKa=4.25). These carboxylic acids may further have a substituent such as a hydroxyl group, an amino group, or a halogen atom. Among these, acetic acid is preferred because of its high safety and ease of availability and handling.
[0031] The carboxylic acid may be a polycarboxylic acid. When the carboxylic acid is a polycarboxylic acid, the coloring resistance of EVOH (a) at high temperatures and the coloring resistance of a melt-molded product of a crushed product of a multilayer structure containing EVOH (a) may be further improved. The polycarboxylic acid compound preferably has three or more carboxy groups. In this case, the coloring resistance may be more effectively improved. The polycarboxylic acid is a compound having two or more carboxy groups in the molecule. In this case, it is preferable that the pKa of at least one carboxy group is in the range of 3.5 to 5.5, and examples of the polycarboxylic acid include oxalic acid (pKa2=4.27), succinic acid (pKa1=4.20), fumaric acid (pKa2=4.44), malic acid (pKa2=5.13), glutaric acid (pKa1=4.30, pKa2=5.40), adipic acid (pKa1=4.43, pKa2=5.50), and the like. =5.41), pimelic acid (pKa1=4.71), phthalic acid (pKa2=5.41), isophthalic acid (pKa2=4.46), terephthalic acid (pKa1=3.51, pKa2=4.82), citric acid (pKa2=4.75), tartaric acid (pKa2=4.40), glutamic acid (pKa2=4.07), aspartic acid (pKa=3.90), etc.
[0032] The barrier layer (A) may further contain a phosphate compound. The lower limit of the content of the phosphate compound is preferably 5 ppm in terms of phosphate radicals. On the other hand, the upper limit of the content of the phosphate compound is preferably 100 ppm in terms of phosphate radicals. By containing the phosphate compound in this range, coloring of the melt-molded product of the EVOH (a) and the pulverized product of the multilayer structure may be suppressed, and thermal stability may be improved. Here, the term "phosphate radical equivalent" refers to the content of phosphorus element (P) in terms of phosphate ion (PO4 3- ) is the value converted into the content.
[0033] As the phosphoric acid compound, various acids such as phosphoric acid and phosphorous acid and their salts can be used. The phosphate may be any of primary phosphate, secondary phosphate, and tertiary phosphate. The cationic species of the phosphate is not particularly limited, but the cationic species is preferably an alkali metal or an alkaline earth metal. Among them, the phosphoric acid compound is preferably sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate.
[0034] The barrier layer (A) may further contain, as an antioxidant, for example, a hindered phenol-based compound having an ester bond or an amide bond. The content of the hindered phenol-based compound is preferably 1000 to 10000 ppm. When the content is 1000 ppm or more, coloring, thickening, and gelation of the resin can be suppressed when the pulverized product of the multilayer structure is melt-molded. The content of the hindered phenol-based compound is more preferably 2000 ppm or more. On the other hand, when the content of the hindered phenol-based compound is 10000 ppm or less, coloring and bleeding out derived from the hindered phenol-based compound can be suppressed. The content of the hindered phenol-based compound is more preferably 8000 ppm or less.
[0035] The hindered phenol compound has at least one hindered phenol group. The hindered phenol group refers to a bulky substituent bonded to at least one carbon atom adjacent to the carbon atom bonded to the hydroxyl group of phenol. The bulky substituent is preferably an alkyl group having 1 to 10 carbon atoms, more preferably a t-butyl group.
[0036] The hindered phenol compound is preferably in a solid state at around room temperature. From the viewpoint of suppressing bleed-out of the compound, the melting point or softening temperature of the hindered phenol compound is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher. From the viewpoint of suppressing bleed-out, the molecular weight of the hindered phenol compound is preferably 200 or higher, more preferably 400 or higher, and even more preferably 600 or higher. Meanwhile, the molecular weight is usually 2000 or lower. From the viewpoint of facilitating mixing with EVOH (a), the melting point or softening temperature of the hindered phenol compound is preferably 200° C. or lower, more preferably 190° C. or lower, and even more preferably 180° C. or lower.
[0037] The hindered phenol compound has an ester bond or an amide bond. Examples of the hindered phenol compound having an ester bond include esters of aliphatic carboxylic acids having a hindered phenol group and aliphatic alcohols, and examples of the hindered phenol compound having an amide bond include amides of aliphatic carboxylic acids having a hindered phenol group and aliphatic amines. Among these, it is preferable that the hindered phenol compound has an amide bond from the viewpoint of facilitating mixing with EVOH (a).
[0038] Specific structures of the hindered phenol compounds include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] commercially available from BASF as Irganox 1010, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)stearylpropionate commercially available as Irganox 1076, 2,2'-thiodiethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] commercially available as Irganox 1035, and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate commercially available as Irganox 1135. octadecyl-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoate, ethylene bis(oxyethylene) bis(3-tert-butyl-4-hydroxy-5-methylbenzenepropanoate) available commercially as Irganox 245, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] available commercially as Irganox 259, and N,N'-hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide] available commercially as Irganox 1098. Among these, N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanamide], commercially available as Irganox 1098, and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], commercially available as Irganox 1010, are preferred, with Irganox 1098 being more preferred.
[0039] The barrier layer (A) may further contain a thermoplastic resin other than EVOH (a). Examples of the thermoplastic resin other than EVOH (a) include various polyolefins (polyethylene, polypropylene, poly1-butene, poly4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-acrylic acid ester copolymers, or modified polyolefins obtained by graft-modifying these with unsaturated carboxylic acids or their derivatives, etc.), various polyamides (nylon 6, nylon 6 / 6, nylon 6 / 66 copolymers, nylon 11, nylon 12, polymetaxylylene adipamide, etc.), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, and modified polyvinyl alcohol resins, etc. The content of the thermoplastic resin in the barrier layer (A) is less than 50% by mass, preferably 30% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and may be 1% by mass or less.
[0040] The proportion of EVOH (a) in the resin constituting the barrier layer (A) is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, or the resin constituting the barrier layer (A) may be composed only of EVOH (a). The proportion of EVOH (a) in the barrier layer (A) is more than 50% by mass, preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, or the barrier layer (A) may be composed substantially only of EVOH (a).
[0041] When the barrier layer (A) contains a component other than EVOH (a), the method for producing the resin composition constituting the barrier layer (A) is not particularly limited, but the barrier layer (A) can be produced by melt-kneading EVOH (a) and other additives (metal ions, etc.) as necessary. The other additives may be blended in a solid state such as powder or as a melt, or may be blended as a solute contained in a solution or a dispersoid contained in a dispersion. As the solution and dispersion, an aqueous solution and an aqueous dispersion are preferable. For the melt-kneading, a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer can be used. The temperature range during melt-kneading can be appropriately adjusted depending on the melting point of the EVOH (a) used, and is usually 150 to 300°C.
[0042] In another embodiment, a master batch containing other additives at a high concentration relative to EVOH(a) can be produced by melt kneading, and the master batch can be dry blended with EVOH(a) that does not substantially contain other additives to produce a multilayer structure. In yet another embodiment, EVOH(a) and other additives can be dry blended to produce a multilayer structure. Dry blending refers to mechanical mixing in the form of powder or pellets. Mixing may be performed using a mixing device such as a tumbler, ribbon mixer, or Henschel mixer, or may be performed by manually stirring, shaking, or the like in a closed container. The mixing temperature may be from room temperature to less than the melting point of EVOH(a), and mixing can be performed under an air atmosphere or a nitrogen atmosphere. Alternatively, the multilayer structure may be produced by adding some components to EVOH(a) in advance and then melt kneading other components that are required as described above. An example of a method of adding some components to EVOH(a) in advance is a method of immersing EVOH(a) as pellets or powder in a solution in which the additive components are dissolved. The solution is preferably an aqueous solution.
[0043] <Adhesive layer (B)> The multilayer structure of the present invention has an adhesive layer (B) containing an adhesive resin (b) as a main component. The adhesive layer (B) has a function of bonding the barrier layer (A) and the thermal adhesive layer (C). Therefore, the adhesive layer (B) is preferably provided between the barrier layer (A) and the thermal adhesive layer (C), and is preferably directly laminated to the barrier layer (A) and the thermal adhesive layer (C).
[0044] The adhesive resin (b) may be, for example, a modified olefin polymer containing a carboxy group obtained by chemically bonding an unsaturated carboxylic acid or its anhydride to an olefin polymer by addition reaction or graft reaction. Examples of the unsaturated carboxylic acid or its anhydride include maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, crotonic acid, itaconic acid, citraconic acid, and hexahydrophthalic anhydride, among which maleic anhydride is preferably used. Specifically, one or a mixture of two or more selected from maleic anhydride graft-modified polyethylene, maleic anhydride graft-modified polypropylene, maleic anhydride graft-modified ethylene-propylene copolymer, maleic anhydride graft-modified ethylene-ethyl acrylate copolymer, and maleic anhydride graft-modified ethylene-vinyl acetate copolymer are preferably used, among which maleic anhydride graft-modified polyethylene is more preferable. The acid value of such adhesive resin (b) is preferably 0.5 to 5 mgKOH / g, more preferably 1 to 4 mgKOH / g. The acid value of the adhesive resin (b) can be measured in accordance with JIS K 0070:1992 using xylene as a solvent.
[0045] The adhesive resin (b) may be a mixture of an unmodified resin (bx) and an acid-modified resin (by). In this case, from the viewpoint of further increasing the mechanical strength, the unmodified resin (bx) preferably contains an ethylene-α-olefin copolymer resin (c) described later, and more preferably is an ethylene-α-olefin copolymer resin (c). Here, when the unmodified resin (bx) contains an ethylene-α-olefin copolymer resin (c), the ethylene-α-olefin copolymer resin (c) contained in the adhesive layer (B) and the ethylene-α-olefin copolymer resin (c) contained in the heat-sealing layer (C) may be the same or different, but are preferably the same. In addition, the ratio (bx / by) of the unmodified resin (bx) and the acid-modified resin (by) in the adhesive resin (b) is preferably 55 / 45 to 95 / 5, and more preferably 65 / 35 to 90 / 10. In this case, as the acid-modified resin (by), a resin having a relatively high degree of acid modification can be preferably used, and its acid value is preferably 5 to 30 mgKOH / g, more preferably 8 to 20 mgKOH / g. In this way, the mechanical strength of the multilayer structure obtained may be further improved while maintaining the necessary interlayer adhesive strength. When the adhesive resin (b) of the present invention is a mixture of the unmodified resin (bx) and the acid-modified resin (by), the unmodified resin (bx) and the acid-modified resin (by) may be melt-kneaded in advance, or the unmodified resin (bx) and the acid-modified resin (by) may be dry-blended. For the melt-kneading, a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer may be used. The temperature range during melt-kneading can be appropriately adjusted depending on the melting points of the unmodified resin (bx) and the acid-modified resin (by) used, and is usually 150 to 300°C. Dry blending refers to mechanically mixing in the form of powder or pellets. The mixing may be performed using a mixing device such as a tumbler, a ribbon mixer, or a Henschel mixer, or may be performed in a sealed container by manually stirring, shaking, etc. The mixing temperature may be from room temperature to below the melting points of the unmodified resin (bx) and the acid-modified resin (by), and the mixing may be performed in an air atmosphere or a nitrogen atmosphere.
[0046] The adhesive layer (B) may contain other components other than the adhesive resin (b) as long as the effect of the present invention is not impaired. Examples of other components include alkali metal ions, polyvalent metal ions, carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, UV absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, bulking agents, pigments, dyes, processing aids, flame retardants, and antifogging agents. The content of other components in the adhesive layer (B) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less. In addition, the adhesive layer (B) may further contain a thermoplastic resin other than the adhesive resin (b). As the thermoplastic resin, the above-mentioned resins exemplified as the thermoplastic resin that may be contained in the barrier layer (A) can be used. The content of the thermoplastic resin in the adhesive layer (B) is less than 50% by mass, preferably less than 30% by mass, more preferably less than 10% by mass, further preferably 5% by mass or less, and may be 1% by mass or less.
[0047] The proportion of the adhesive resin (b) in the resin constituting the adhesive layer (B) is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, and the resin constituting the adhesive layer (B) may be composed only of the adhesive resin (b). The proportion of the adhesive resin (b) in the adhesive layer (B) is more than 50% by mass, preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, and the adhesive layer (B) may be substantially composed only of the adhesive resin (b).
[0048] <Heat-sealing layer (C)> The multilayer structure of the present invention has a density of 0.880 to 0.930 g / cm 3 The heat-sealing layer (C) contains, as a main component, an ethylene-α-olefin copolymer resin (c), which is a thermosealing layer that functions as a sealing layer when forming a packaging material, and also functions to increase various mechanical strengths, such as resistance to breakage due to dropping, puncture strength, and tensile strength.
[0049] The density of the ethylene-α-olefin copolymer resin (c) is 0.880 to 0.930 g / cm 3 When the density is within the above range, the resulting multilayer structure is flexible and has excellent handleability, and in addition to resistance to bag breakage due to dropping, various mechanical strengths such as puncture strength and elongation and tensile strength and elongation are improved. The lower limit of the density is 0.890 g / cm 3 is preferred, and 0.900 g / cm 3 More preferably, 0.905 g / cm 3 More preferably, 0.910 g / cm 3 The upper limit of the density is 0.925 g / cm 3 is preferred, and 0.920 g / cm 3 is more preferred.
[0050] The MFR (190°C, 2.16 kg load) of the ethylene-α-olefin copolymer resin (c) is preferably 0.5 to 5.0 g / 10 min. When the MFR is in the above range, the ethylene-α-olefin copolymer resin (c) has excellent melt processability, and the obtained multilayer structure has improved mechanical strengths such as drop bag breakage resistance, puncture strength and elongation, and tensile strength and elongation. The lower limit of the MFR is more preferably 0.7 g / 10 min. The upper limit of the MFR is more preferably 4.0 g / 10 min, and even more preferably 2.0 g / 10 min. The MFR is measured at 190°C and under a load of 2.16 kg in accordance with JIS K 7210 (2014).
[0051] The ethylene-α-olefin copolymer resin (c) is a resin obtained by polymerizing ethylene with an α-olefin having 3 or more carbon atoms. Examples of the α-olefin having 3 or more carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, and 4-methyl-1-pentene. The ethylene-α-olefin copolymer resin (c) is preferably a linear low-density polyethylene obtained by polymerizing ethylene with an α-olefin having 6 or more carbon atoms, and may be a linear low-density polyethylene obtained by polymerizing ethylene with an α-olefin having 8 or more carbon atoms. When the carbon number of the α-olefin copolymerized with ethylene is relatively large, various mechanical strengths such as pin puncture strength and tensile strength may be particularly improved. The upper limit of the carbon number of the α-olefin having 3 or more carbon atoms is not particularly limited, but the carbon number is generally 12 or less.
[0052] In addition, it is preferable to use a metallocene catalyst as the polymerization catalyst. The linear low-density polyethylene polymerized using a metallocene catalyst is produced by copolymerizing ethylene and an α-olefin in the presence of a catalyst formed from a compound of a transition metal of Group 4 of the periodic table, preferably zirconium, having at least one ligand having a cyclopentadienyl skeleton, an organoaluminum oxy compound, and various components added as necessary. The linear low-density polyethylene polymerized using a metallocene catalyst has excellent melt moldability, and the multilayer structure obtained has an excellent balance of heat resistance, flexibility, and mechanical strength.
[0053] Linear low-density polyethylene obtained by polymerizing ethylene and an α-olefin having 6 or more carbon atoms using a metallocene catalyst is commercially available as industrially produced polyethylene, such as "Evolue (trademark)" (Prime Polymer Co., Ltd.), "Sumikasen (trademark)" (Sumitomo Chemical Co., Ltd.), "Yumerit (trademark)" (Ube Maruzen Polyethylene Co., Ltd.), and "Elite (trademark)" (Dow Chemical Co., Ltd.).
[0054] The heat-sealing layer (C) may contain other components other than the ethylene-α-olefin copolymer resin (c) as long as the effects of the present invention are not impaired. Examples of other components include alkali metal ions, polyvalent metal ions, carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, UV absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, bulking agents, pigments, dyes, processing aids, flame retardants, and antifogging agents. The content of other components in the heat-sealing layer (C) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less. The heat-sealing layer (C) may further contain a thermoplastic resin other than the ethylene-α-olefin copolymer resin (c). As the thermoplastic resin, the above-mentioned resins exemplified as the thermoplastic resin that may be contained in the barrier layer (A) can be used. The content of the thermoplastic resin in the heat-sealing layer (C) is less than 50% by mass, preferably less than 30% by mass, more preferably less than 10% by mass, further preferably 5% by mass or less, and may be 1% by mass or less.
[0055] The proportion of the ethylene-α-olefin copolymer resin (c) in the resin constituting the heat-sealing layer (C) is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, and the resin constituting the heat-sealing layer (C) may be composed only of the ethylene-α-olefin copolymer resin (c). The proportion of the ethylene-α-olefin copolymer resin (c) in the heat-sealing layer (C) is more than 50% by mass, preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more, and the heat-sealing layer (C) may be substantially composed only of the ethylene-α-olefin copolymer resin (c).
[0056] The method for producing the resin composition constituting the heat-sealing layer (C) is not particularly limited, but it can be produced by melt-kneading the ethylene-α-olefin copolymer resin (c) and, if necessary, other additives. For the melt-kneading, a known mixing or kneading device such as a kneader-ruder, an extruder, a mixing roll, or a Banbury mixer can be used. The temperature range during melt-kneading can be appropriately adjusted depending on the melting point of the ethylene-α-olefin copolymer resin (c) used, and is usually 150 to 300°C.
[0057] In another embodiment, a master batch containing other additives at a high concentration as necessary for the ethylene-α-olefin copolymer resin (c) is produced by melt kneading, and the master batch is dry-blended with an ethylene-α-olefin copolymer resin (c) that does not substantially contain other additives, and can be used to produce a multilayer structure. In yet another embodiment, the ethylene-α-olefin copolymer resin (c) and other additives can be dry-blended to produce the heat-sealable layer (C). Dry blending refers to mechanical mixing in the form of powder or pellets. Mixing may be performed using a mixing device such as a tumbler, ribbon mixer, or Henschel mixer, or may be performed by manually stirring, shaking, or the like in a sealed container. The mixing temperature may be from room temperature to less than the melting point of the ethylene-α-olefin copolymer resin (c), and mixing can be performed under an air atmosphere or a nitrogen atmosphere.
[0058] The sealant layer (X) of the present invention has a barrier layer (A), an adhesive layer (B) and a heat-sealing layer (C). It is preferable that at least one pair of the barrier layer (A) and the adhesive layer (B) are laminated adjacent to each other. This makes it possible to obtain a multilayer structure having high gas barrier properties and recyclability, as well as excellent mechanical strength and stability.
[0059] The lamination method for producing the sealant layer (X) may be a conventional co-extrusion method in which each resin is extruded from a separate die or a common die and laminated. As the die, either a circular die or a T-die may be used. The molding temperature during melt molding may be appropriately adjusted based on the melting point and melt viscosity of the resin used, and is often selected from the range of 150 to 300°C. From the viewpoint of maintaining the heat seal strength when the multilayer structure of the present invention is molded for use as a soft packaging material, it is preferable that the sealant layer (X) is a non-oriented layer.
[0060] The total thickness of the sealant layer (X) of the present invention is preferably 15 to 300 μm, more preferably 25 to 250 μm, further preferably 35 to 200 μm, and particularly preferably 45 to 150 μm. When the total thickness is within the above range, the sealant layer (X) of the present invention is lightweight and flexible, and is therefore preferably used for flexible packaging. In addition, the amount of resin used in the sealant layer (X) is small, and the environmental load is suppressed.
[0061] The lower limit of the thickness of the barrier layer (A) is preferably 1 μm. When the lower limit of the thickness of the barrier layer (A) is within the above range, the multilayer film exhibits sufficient gas barrier properties. The upper limit of the thickness of the barrier layer (A) is preferably 30 μm, more preferably 25 μm, even more preferably 20 μm, and particularly preferably 15 μm. When the upper limit of the thickness of the barrier layer (A) is within the above range, the recyclability when the sealant layer (X) or the multilayer structure is recovered and reused is improved. In addition, from the viewpoint of suppressing a decrease in resistance to drop-breakage of a bag, the thickness of the barrier layer (A) may be preferably 5 μm or less, more preferably 4 μm or less, and even more preferably 2 μm or less. When the thickness of the barrier layer (A) is 5 μm or less, in order to maintain good gas barrier properties, the ethylene unit content of EVOH (a) is preferably 33 mol % or less, more preferably 28 mol % or less, and even more preferably 25 mol % or less. The barrier layer (A) is necessary from the viewpoint of improving the gas barrier property, but it has been found that a multilayer structure including the barrier layer (A) tends to have a decreased resistance to bag breakage due to dropping, particularly at low temperatures. As a result of intensive studies, the present inventors have found that the decrease in the resistance to bag breakage due to dropping can be minimized by reducing the thickness of the barrier layer (A).
[0062] The thickness of the adhesive layer (B) is preferably 1 to 20 μm, more preferably 2 to 10 μm. When the thickness of the adhesive layer (B) is within the above range, the interlayer adhesion between the barrier layer (A) and the thermal adhesive layer (C) is increased, and the recyclability when the sealant layer (X) or the multilayer structure is recovered and reused is improved.
[0063] The thickness of the heat-sealing layer (C) is preferably 15 to 300 μm, more preferably 30 to 200 μm, and even more preferably 40 to 150 μm. When the thickness of the heat-sealing layer (C) is within the above range, the recyclability, mechanical strength, and water vapor barrier property are improved.
[0064] In the sealant layer (X) of the present invention, the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is preferably 0.10 or less. When this ratio is within the above range, the recyclability and mechanical strength are improved. The upper limit of the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is more preferably 0.08, even more preferably 0.05, and particularly preferably 0.04. The lower limit of the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is not particularly limited, but is preferably 0.005 in order to exhibit sufficient gas barrier properties. On the other hand, in the multilayer structure of the present invention, the ratio of the thickness of the heat-sealing layer (C) to the total thickness of all layers is preferably 0.60 or more, more preferably 0.70 or more, even more preferably 0.80 or more, and may be 0.99 or less. When this ratio is within the above range, the recyclability, mechanical strength, and water vapor barrier properties are improved.
[0065] The layer structure of the sealant layer (X) of the present invention is not particularly limited as long as it has a barrier layer (A), an adhesive layer (B) and a heat-sealing layer (C) and the heat-sealing layer (C) is exposed, and if the heat-sealing layer (C) is expressed as (C), the adhesive resin layer (B) as (B), and the barrier layer (A) as (A), and " / " indicates direct lamination, examples of the layer structure include (C) / (B) / (A) / (B) / (C), (C) / (B) / (A), etc. In addition to the above layer structure, another layer may be further included, and when a plurality of the barrier layers (A), adhesive layers (B), and heat-sealing layers (C) are used, different types of resins may be used for each.
[0066] <Base material layer (Y)> The multilayer structure of the present invention has a base layer (Y) containing polypropylene (y) as a main component having a melting point of 140°C or more as measured by a differential scanning calorimeter (DSC), and having a modulus of elasticity in both the machine direction and the width direction at 23°C and 50% RH of 1000 MPa or less. In the present specification, "polypropylene" refers to a homopolymer of propylene, a copolymer of 80 mol% or more of propylene and 20 mol% or less of ethylene or α-olefin monomer, and a copolymer of 90 mol% or more of propylene and less than 10 mol% of a non-olefin monomer whose functional group does not contain atoms other than carbon atoms, oxygen atoms, and hydrogen atoms. The base layer (Y) containing polypropylene (y) as a main component having a melting point of 140°C or more as measured by a differential scanning calorimeter (DSC) can improve the heat sealability of the multilayer structure of the present invention. The melting point is preferably 150°C or more, more preferably 160°C or more, and may be 165°C or more. The melting point may be 170°C or less. In addition, when the base layer (Y) has the above melting point and the elastic modulus in both the machine direction and the width direction under the condition of 23°C and 50% RH is 1000 MPa or less, a multilayer structure having improved resistance to drop-breakage under low temperature conditions can be obtained. It is preferable that the base layer (Y) is not substantially stretched in the uniaxial or biaxial directions. Here, some orientation during film formation (for example, orientation as if stretched 1.1 times) is considered to be substantially not stretched. It is common to increase the elastic modulus of the base layer (Y) to improve the resistance to drop-breakage, but according to the present invention, the elastic modulus of the base layer (Y) is set to a certain value or less, thereby improving the resistance to drop-breakage, particularly at low temperatures. In addition, the elastic modulus in the machine direction is preferably 800 MPa or less, more preferably 700 MPa or less, and may be 600 MPa or less or 500 MPa or less. The elastic modulus in the machine direction may be 400 MPa or more. The elastic modulus in the width direction is preferably 800 MPa or less, more preferably 700 MPa or less, even more preferably 600 MPa or less, and may be 500 MPa or less. The elastic modulus in the width direction may be 400 MPa or more. The elastic modulus in the flow direction and width direction can be controlled by the temperature conditions and cooling conditions during melt extrusion, the take-up speed, the heat treatment conditions after film formation, etc.
[0067] The haze of the base layer (Y) measured according to JIS K 7136:2000 is preferably 35% or less. When the haze is in the above range, the appearance of the base layer (Y) tends to be improved when it is printed. The haze is more preferably 15% or less, more preferably 10% or less, and may be 7% or less. The haze may be 1% or more. When the crystallization degree of the polypropylene (y) is increased to improve the heat resistance of the base layer (Y), the haze tends to increase, but the haze may be reduced while maintaining the heat resistance by using a crystal nucleating agent or the like during melt extrusion. However, it may be difficult to provide a base layer (Y) that has all of the above-mentioned melting point, modulus, and haze in a more suitable range, and it has been found that when a base layer (Y) having a low haze (for example, 15% or less) is used, the heat sealability and drop-breakage strength may be reduced. As a result of intensive research, the present inventors have found that when a base layer (Y) having low haze is used, by using a barrier layer (A) having a small thickness (for example, 5 μm or less), it is possible to obtain a multilayer structure having a good appearance while maintaining appropriate heat sealability and drop bag breakage strength.
[0068] The proportion of polypropylene (y) in the resin constituting the base layer (Y) is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, may be 97% by mass or more or 99% by mass or more, and the resin constituting the base layer (Y) may be composed of polypropylene (y) alone. The content of polypropylene (y) in the base layer (Y) must be more than 50% by mass, preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, may be 97% by mass or more, 99% by mass or more, and the base layer (Y) may be substantially composed of polypropylene (y) alone.
[0069] The method for forming the substrate layer (Y) is not particularly limited, but the substrate layer (Y) is generally formed by melt extrusion using an extruder. As the die, either a circular die or a T-die can be used. During the film formation, it is preferable that the substrate layer (Y) is not substantially stretched in the uniaxial or biaxial directions.
[0070] From the viewpoint of industrial productivity, the thickness of the base layer (Y) is preferably 10 to 100 μm. Furthermore, from the viewpoint of achieving a balance between the mechanical strength, water vapor barrier property, and production costs of the multilayer structure, the thickness of the base layer (Y) is more preferably 20 to 80 μm, further preferably 25 to 75 μm, and may be 35 to 65 μm.
[0071] The layer structure of the base layer (Y) of the present invention is not particularly limited as long as it contains polypropylene (y) as a main component, and may be a single layer or multiple layers. From the viewpoints of production costs and imparting functionality, however, it is generally a single layer to five layers.
[0072] <Multilayer structure> The multilayer structure of the present invention is a multilayer structure in which a sealant layer (X) and a base layer (Y) are laminated, and has a heat-sealing layer (C) of the sealant layer (X) on the outermost surface. Since the heat-sealing layer (C) is disposed on the outermost surface of the multilayer structure, the multilayer structure of the present invention can be easily heat-sealed when used as a packaging material or the like. In addition, the multilayer structure of the present invention preferably does not have a resin layer having a thickness of 10 μm or more and containing a resin having a melting point of 200° C. or more as a main component, and a metal layer having a thickness of 1 μm or more. That is, it is preferable that the EVOH (a), the adhesive resin (b), the ethylene-α-olefin copolymer (c) and the polypropylene (y) all have melting points less than 200° C. Here, "does not have a resin layer having a thickness of 10 μm or more and containing a resin having a melting point of 200° C. or more as a main component, and a metal layer having a thickness of 1 μm or more" means that it does not have a resin layer having a thickness of 10 μm or more and containing a resin having a melting point of 200° C. or more as a main component, and does not have a metal layer having a thickness of 1 μm or more. By not having a resin layer having a thickness of 10 μm or more and containing a resin having a melting point of 200° C. or more as a main component and a metal layer having a thickness of 1 μm or more, when the crushed product of the multilayer structure is melt-molded, it is possible to suppress uneven mixing with other components. In other words, recyclability is improved. Here, the metal layer is a layer having continuous and discontinuous surfaces made of metal, such as aluminum foil. From the viewpoint of further improving recyclability, the thickness of each layer containing a resin having a melting point of 200° C. or more as a main component is preferably 7 μm or less, and may be 5 μm or less.
[0073] The upper limit of the total thickness of the multilayer structure of the present invention is preferably 300 μm. With a total thickness in the above range, the multilayer structure of the present invention is lightweight and flexible, and is therefore preferably used for soft packaging applications. Furthermore, the amount of resin used in the multilayer structure is small, and environmental impact is suppressed. The upper limit of the total thickness of the multilayer structure of the present invention is more preferably 250 μm, and even more preferably 200 μm. From the viewpoint of maintaining the mechanical strength and water vapor barrier property of the multilayer structure of the present invention, the lower limit of the total thickness is preferably 30 μm, more preferably 50 μm, even more preferably 100 μm, and particularly preferably 150 μm.
[0074] The thickness of each layer in the multilayer structure of the present invention may be adjusted appropriately depending on the application, but from the viewpoint of suppressing coloration when the pulverized material is melt-molded, improving thermal stability during melt molding, and suppressing the occurrence of bumps, the ratio of the total thickness of the layers containing polyolefin resin as a main component to the total thickness of the multilayer structure is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and particularly preferably 0.95 or more. As the polyolefin resin, polyethylene, ethylene-α-olefin copolymer resin, polypropylene, and acid-modified resins thereof are preferred, and for example, ethylene-α-olefin copolymer resin (c), polypropylene (y), adhesive resin (b) in the case of polyolefin resin, etc., correspond to the polyolefin resin.
[0075] The multilayer structure of the present invention has a puncture strength S measured according to JIS Z1707:2019 under conditions of 23°C and 50% RH, and a puncture strength S of the sealant layer (X) measured according to JIS Z1707:2019 under conditions of 23°C and 50% RH. X Difference with (SS X ) is preferably 3.0N or more, more preferably 3.5 or more, and even more preferably 4.0 or more. X ) may be 10 N or less. The puncture strength S of the multilayer structure of the present invention is preferably 9 N or more, more preferably 10 N or more, even more preferably 11 N or more, particularly preferably 11.5 N or more, and may be 12 N or more or 12.5 N or more. The puncture strength S may be 20 N or less. The puncture strength can be adjusted, for example, by the type of polypropylene (y) used in the base layer (Y), the thickness of each layer of the multilayer structure, the layer configuration of the multilayer structure, etc.
[0076] The oxygen transmission rate (OTR) of the multilayer structure of the present invention under conditions of 20° C. and 65% RH is not particularly limited and may be adjusted depending on the application. 2 ·day·atm) or less. A multilayer structure having an OTR in this range has excellent gas barrier properties and is suitable for use as a packaging material. The OTR is preferably 2 cc / (m 2·day·atm) or less is preferable, and 1.5cc / (m 2 ·day·atm) or less is more preferable, and 0.5cc / (m 2 ·day·atm) or less. OTR is 0.1cc / (m 2 The OTR may be measured in accordance with JIS K 7126-2 (isobaric method; 2006), and specifically, the method described in the examples is employed.
[0077] The water vapor transmission rate (WVTR) of the multilayer structure of the present invention under conditions of 40° C. and 90% RH is not particularly limited and may be adjusted depending on the application. 2 ·day) or less. Multilayer films with a WVTR in this range have excellent water vapor barrier properties and are suitable for use as packaging materials. 2 ·day) or less is more preferable, and 2.5g / (m 2 ·day) or less. The WVTR is 1.0 g / (m 2 ·day) or more. WVTR is measured in accordance with JIS K 7129-2 (infrared sensor method; 2019), and specifically, the method described in the examples is adopted.
[0078] The method of laminating the base layer (Y) on the sealant layer (X) is not particularly limited, and examples thereof include extrusion lamination, coextrusion lamination, dry lamination, etc., but dry lamination is preferred from the viewpoint of handling. When laminating the base layer (Y) on the sealant layer (X), an adhesive layer may be provided. The adhesive layer may be an adhesive layer (B) or an adhesive layer (Z) that can be formed by applying a known adhesive and drying it. As the known adhesive, for example, a two-liquid reactive polyurethane adhesive in which a polyisocyanate component and a polyol component are mixed and reacted is preferred. The thickness of the adhesive layer (Z) is not particularly limited, but is preferably 2 to 7 μm, more preferably 3 to 5 μm.
[0079] The multilayer structure of the present invention may have layers other than those described above, provided that the effects of the present invention are not impaired. The other layers are preferably layers other than a resin layer having a thickness of 10 μm or more and containing a resin having a melting point of 200° C. or more as a main component, or a metal layer having a thickness of 1 μm or more, and examples thereof include a resin layer containing a thermoplastic resin as a main component. The thermoplastic resin is not particularly limited, and examples thereof include polyolefin, polyamide, polyester, polystyrene, polyvinyl chloride, polyvinylidene chloride, acrylic resin, polycarbonate, chlorinated polyethylene, chlorinated polypropylene, and the like. Another example of the other layer is a recovery layer. In particular, it is preferable to reuse a recovery composition containing the recovered material of the multilayer structure of the present invention described later as a part or all of the recovery layer. Another example of the other layer is a printing layer. The printing layer may be included at any position in the multilayer structure of the present invention. Examples of the printing layer include a film obtained by applying a solution containing a pigment or dye, and optionally a binder resin, and drying it. Examples of the coating method for the printing layer include gravure printing, as well as various coating methods using a wire bar, a spin coater, a die coater, and the like. The thickness of the printed layer is not particularly limited, but is preferably 0.5 to 10 μm, and more preferably 1 to 4 μm.
[0080] It is preferable to recover and reuse the ends and defective products generated during the production of the multilayer structure of the present invention. It is also preferable to recover and reuse multilayer structures distributed on the market. In this case, a recovery method in which the multilayer structure is crushed and then melt-molded is generally used.
[0081] In recovering the multilayer structure of the present invention, the recovered material of the multilayer structure of the present invention is first pulverized. The pulverized recovered material may be melt-molded as it is to obtain a recovered composition, or may be melt-molded together with other components as necessary to obtain a recovered composition. When the recovered composition is obtained by melt-molding together with other components, the other components are preferably polyolefin resins, more preferably polypropylene resins, polyethylene resins, or mixtures thereof. The pulverized recovered material may be directly used to manufacture a molded product such as a multilayer structure, or the pulverized recovered material may be melt-pelletized to obtain pellets of the recovered composition, and the pellets may be used to manufacture a molded product. The melt-molding method of the recovered composition may include extrusion molding, inflation molding, blow molding, melt spinning, injection molding, etc. The molding temperature during melt molding may be appropriately adjusted based on the melting point and melt viscosity of the resin used, and is often selected from the range of 150 to 300 ° C. The recovered composition may contain unused resin, but the content of the recovered material in the recovered composition is preferably 10 mass % or more, more preferably 20 mass % or more, and may be 30 mass % or more. The content of EVOH (a) in the recovered composition is preferably 20% by mass or less, more preferably 10% by mass or less, and may be 5% by mass or less.
[0082] Since the multilayer structure of the present invention has excellent gas barrier properties, heat seal properties, drop-breakage resistance, and recyclability, it can be suitably used as a variety of packaging materials such as food packaging, pharmaceutical packaging, industrial chemical packaging, and agricultural chemical packaging, but it can also be used for a wider range of applications and is not limited to these applications.
[0083] A package obtained by filling the packaging material with contents is a preferred embodiment of the packaging material. Contents that can be filled include, but are not limited to, beverages such as wine and fruit juice, foods such as fruits, nuts, vegetables, meat products, baby foods, coffee, jams, mayonnaise, ketchup, edible oils, dressings, sauces, foods boiled in soy sauce, dairy products, and other contents that are prone to deterioration in the presence of oxygen, such as medicines, cosmetics, and gasoline. EXAMPLES
[0084] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples in any way.
[0085] <Materials used> ·Base material layer (Y) Y-1: Non-stretched PP film "RXC-22 (50μm)" manufactured by Mitsui Chemicals Tocello Co., Ltd. Y-2: Toray Film Processing Co., Ltd.'s non-stretched PP film "Torayfan (trademark) NOZK93KM (70 μm)" Y-3: Toray Film Processing Co., Ltd.'s non-stretched PP film "Torayfan (trademark) NOZK100 (70 μm)" Y-4: Toray Film Processing Co., Ltd.'s non-stretched PP film "Torayfan (trademark) NO3951 (60 μm)" YC-1: Biaxially oriented PP film "U-1 (40 μm)" manufactured by Mitsui Chemicals Tocello Co., Ltd. YC-2: Biaxially oriented HDPE film "Ethy-Lyte(TM) 25HD200" manufactured by Jindal Poly Films Ltd. YC-3: Non-stretched PE film "TUX (trademark) HZR-2 (50 μm)" manufactured by Mitsui Chemicals Tocello Co., Ltd. EVOH(a) a-1: EVOH, ethylene unit content 32 mol%, saponification degree 99.9 mol%, sodium acetate 250 ppm in sodium ion equivalent, magnesium acetate 40 ppm in magnesium ion equivalent, phosphate ion 20 ppm in phosphate radical equivalent, boric acid 200 ppm in boron element equivalent, MFR (190°C, 2.16 kg load) 1.6 g / 10 min a-2: EVOH, ethylene unit content 32 mol%, saponification degree 99.9 mol%, sodium acetate 250 ppm in sodium ion equivalent, magnesium acetate 40 ppm in magnesium ion equivalent, phosphate ion 20 ppm in phosphate radical equivalent, MFR (190°C, 2.16 kg load) 1.6 g / 10 min a-3: EVOH, ethylene unit content 24 mol%, saponification degree 99.9 mol%, sodium acetate 250 ppm in sodium ion equivalent, magnesium acetate 40 ppm in magnesium ion equivalent, phosphate ion 20 ppm in phosphate radical equivalent, MFR (210°C, 2.16 kg load) 2.5 g / 10 min a-4: EVOH, ethylene unit content 27 mol%, saponification degree 99.9 mol%, sodium acetate 250 ppm in sodium ion equivalent, magnesium acetate 40 ppm in magnesium ion equivalent, phosphate ion 20 ppm in phosphate radical equivalent, MFR (210°C, 2.16 kg load) 3.0 g / 10 min a-5: EVOH, ethylene unit content 44 mol%, saponification degree 99.9 mol%, sodium acetate 250 ppm in sodium ion equivalent, magnesium acetate 40 ppm in magnesium ion equivalent, phosphate ion 20 ppm in phosphate radical equivalent, MFR (190°C, 2.16 kg load) 5.0 g / 10 min ·Adhesive resin (b) b-1: Maleic anhydride modified polyethylene "Admer (trademark) NF518" manufactured by Mitsui Chemicals Inc. (MFR (190°C, 2.16 kg load) 3.1 g / 10 min, density 0.91 g / cm 3 , acid value 1.10mgKOH / g) b-2: Maleic anhydride modified polypropylene "Admer (trademark) QF500" manufactured by Mitsui Chemicals Inc. (MFR (230°C, 2.16 kg load) 3.0 g / 10 min, density 0.90 g / cm 3 , acid value 1.12mgKOH / g) Ethylene-α-olefin copolymer resin (c) c-1: Linear low-density polyethylene "Evolue (trademark) SP1510" manufactured by Prime Polymer Co., Ltd. (ethylene and 1-hexene polymerized with a metallocene catalyst, MFR (190°C, 2.16 kg load) 1.0 g / 10 min, density 0.915 g / cm 3 ) c-2: Linear low-density polyethylene "Evolue (trademark) SP0510" manufactured by Prime Polymer Co., Ltd. (ethylene and 1-hexene polymerized with a metallocene catalyst, MFR (190°C, 2.16 kg load) 1.2 g / 10 min, density 0.903 g / cm 3 ) c-3: Linear low-density polyethylene "Evolue (trademark) SP2510" manufactured by Prime Polymer Co., Ltd. (ethylene and 1-hexene polymerized with a metallocene catalyst, MFR (190°C, 2.16 kg load) 1.5 g / 10 min, density 0.923 g / cm 3 ) cC-1: Linear low-density polyethylene "Evolue (trademark) SP4030" manufactured by Prime Polymer Co., Ltd. (ethylene and 1-hexene polymerized with a metallocene catalyst, MFR (190°C, 2.16 kg load) 3.8 g / 10 min, density 0.938 g / cm 3 ) cC-2: Polypropylene "Novatec (trademark) PP EA7AD" manufactured by Japan Polypropylene Corporation (MFR (230°C, 2.16 kg load) 1.4 g / 10 min, density 0.90 g / cm 3 )
[0086] <Evaluation method> (1) Differential scanning calorimetry of the base layer (Y) For the base layer (Y) used in the examples and comparative examples, the maximum endothermic peak temperature when the temperature was raised from 20°C to 220°C at 10°C / min using a differential scanning calorimeter DSC ("Q2000" manufactured by TA Instruments) was determined as the melting point of the polypropylene (y) constituting the base layer (Y).
[0087] (2) Elastic modulus measurement of the base layer (Y) The substrate layer (Y) used in the examples and comparative examples was conditioned for 24 hours under conditions of 23°C and 50% RH, then cut into a width of 15 mm, and the elastic modulus was measured at a tensile speed of 5 mm / min in accordance with ASTM D-638. The measurement was performed on 10 samples each in the machine direction (MD) and the cross direction (TD), and the average value was calculated.
[0088] (3) Haze measurement of the base layer (Y) A square sample of 10 cm × 10 cm was cut out from the base layer (Y) used in the examples and comparative examples. Next, the haze of the cut sample was measured using a Boyck integrating sphere light transmittance / total light reflectance meter ("HR-100" manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7136: 2000.
[0089] (4) Measurement of puncture strength of sealant layer (X) and multi-layer structure The sealant layer (X) used in the examples and comparative examples and the multilayer structures obtained in the examples and comparative examples were conditioned for 24 hours under conditions of 23°C and 50% RH, and then the breaking strength was measured under the same conditions when a needle with a tip diameter of 1 mm was pierced at a speed of 50 mm / min. The measurement was performed 10 times at different locations, and the average value was used as the measurement result. Note that the needle was pierced from the base layer (Y) side of the multilayer structures.
[0090] (5) Appearance characteristics of multi-layered structures (print clarity) The multilayer structures obtained in the Examples and Comparative Examples were visually observed from the substrate layer (Y) side and rated according to the following criteria. Judgment criteria A: The print looks vivid. B: The print appears slightly dull. C: The print looks dull. D: The print looks very dull. E: The print appears extremely dull.
[0091] (6) Heat sealability of multi-layer structures The multilayer structures obtained in the Examples and Comparative Examples were cut into two A4 size pieces, the sealant layers (X) were stacked together, and one side was heat sealed at 150°C for 2 seconds using a hot plate sealer. The sealed area was then visually observed and evaluated according to the following criteria. Judgment criteria A: Good appearance B: Slight whitening is observed. C: Slight whitening or voids are observed. D: Significant whitening, voids or deformations are observed. E: Severe whitening, voids or deformations are observed.
[0092] (7) Measurement of oxygen transmission rate of multi-layer structure The oxygen transmission rate was measured using the multilayer structures obtained in the examples and comparative examples, with one side being the oxygen supply side and the other side being the carrier gas side. Specifically, using an oxygen transmission rate measuring device ("MOCON OX-TRAN2 / 21" manufactured by Modern Controls), the oxygen transmission rate (unit: cc / (m)) was measured under the conditions of temperature 20°C, humidity 65% RH on the oxygen supply side, humidity 65% RH on the carrier gas side, oxygen pressure 1 atm, and carrier gas pressure 1 atm in accordance with JIS K 7126-2 (isobaric method; 2006). 2 The oxygen permeability (O2) was measured at 5.0 cc / (m2 / day·atm). During the measurement, the base layer (Y) side of the multilayer structure was the oxygen supply side. Nitrogen gas containing 2% by volume of hydrogen gas was used as the carrier gas. The oxygen permeability was 5.0 cc / (m2 / day·atm). 2 When the gas barrier strength was 100% (100 / day·atm) or higher, the gas barrier properties were determined to be insufficient.
[0093] (8) Measurement of water vapor transmission rate of multi-layer structure Using the multilayer structures obtained in the examples and comparative examples, the water vapor transmission rate was measured with one side being the water vapor supply side and the other side being the carrier gas side. Specifically, using a water vapor transmission rate measuring device ("MOCON PERMATRAN W3 / 33" manufactured by Modern Controls), the water vapor transmission rate (unit: g / (m)) was measured under conditions of a temperature of 40°C, a humidity of 90% RH on the water vapor supply side, and a humidity of 0% RH on the carrier gas side in accordance with JIS K 7129-2 (infrared sensor method; 2019). 2 ·day) was measured. During the measurement, the base layer (Y) side of the multilayer structure was set as the carrier gas side. Nitrogen gas was used as the carrier gas.
[0094] (9) Drop-break resistance of multi-layered structure (at room temperature) The multilayer structures obtained in the examples and comparative examples were cut into two pieces of A4 size, the sealant layers (X) were stacked together, and three sides were heat-sealed at a width of 5 mm using an impulse sealer. Next, 1.2 L of water was filled from the opening, and the remaining sides were heat-sealed using an impulse sealer to create a water-filled bag. This water-filled bag was repeatedly dropped upright from a height of 1.5 m under conditions of 25°C and 70% RH, and the number of times water leakage was confirmed was measured. The same test was performed five times, and the average value was adopted as the measurement result. The results were judged according to the following criteria. D and E are unacceptable criteria. Judgment criteria A: 12 or more times B: 8 to less than 12 times C: 4 to less than 8 times D: 2 to 4 times E: Less than twice
[0095] (10) Drop-break resistance of multi-layered structures (low temperature) The multilayer structures obtained in the examples and comparative examples were cut into two pieces of A4 size, the sealant layers (X) were stacked together, and three sides were heat-sealed at a width of 5 mm using an impulse sealer. Next, 1.2 L of water was filled from the opening, and the remaining sides were heat-sealed using an impulse sealer to create a water-filled bag. After leaving this water-filled bag in a refrigerator at 4°C for 24 hours, it was repeatedly allowed to freely fall in an upright direction from a height of 1.5 m under conditions of 25°C and 70% RH, and the number of times water leakage was confirmed was measured. The same test was performed five times, and the average value was adopted as the measurement result. The results were judged according to the following criteria. D and E are unacceptable criteria. Judgment criteria A: 8 or more times B: 5 to less than 8 times C: 3 to less than 5 times D: 2 or more times but less than 3 times E: Less than twice
[0096] (11)Recyclability evaluation of multi-layer structures The multilayer structures obtained in the examples and comparative examples were pulverized into pieces of 4 mm square or less. The pulverized pieces were mixed with a low-density polyethylene resin "Novatec (trademark) LD LJ400" (MFR (190°C, 2.16 kg load) 1.5 g / 10 min, density 0.921 g / cm) manufactured by Japan Polyethylene Corporation. 3 ) and Japan Polypropylene Corporation's polypropylene "Novatec (trademark) PP EA7AD" (MFR (230°C, 2.16 kg load) 1.4 g / 10 min, density 0.90 g / cm 3 ) was blended in a mass ratio (ground material / polyethylene resin / polypropylene resin) of 50 / 25 / 25, and a monolayer film with a thickness of 50 μm was formed under the extrusion conditions shown below. The thickness of the monolayer film was adjusted by appropriately changing the screw rotation speed and take-up roll speed. As a control, a monolayer film with a thickness of 50 μm was similarly obtained without blending the ground material ((polyethylene resin / polypropylene resin) 50 / 50). Extruder: Toyo Seiki Co., Ltd. single screw extruder Screw diameter: 20mmφ (L / D=20, compression ratio=3.5, full flight type) Extrusion temperature: feeding section / compression section / metering section / die = 180 / 230 / 230 / 230℃ Take-off roll temperature: 80℃ The occurrence of bumps in the obtained monolayer film was evaluated on the following 5-level scale of A to E, where E is an unacceptable standard. Judgment criteria A: Compared to the control, the amount of pimples was almost the same. B: The amount of small particles was slightly more than in the control. C: Compared to the control, the amount of small bumps was greater. D: Compared to the control, there was a greater amount of large bumps. E: The amount of large particles was significantly greater than in the control.
[0097] <Example> Example 1 EVOH (a-1) was used as the material for the barrier layer (A), adhesive resin (b-1) was used as the material for the adhesive layer (B), and ethylene-α-olefin copolymer resin (c-1) was used as the material for the heat-sealing layer (C). A multilayer film (sealant layer (X-1)) having a layer thickness and layer structure of (C) / (B) / (A) / (B) / (C)=60μm / 4μm / 6μm / 4μm / 60μm was produced using a 5-layer co-extrusion cast film production equipment with a width of 300mm. The film production conditions at this time are shown below. Extrusion temperature of barrier layer (A): feeding section / compression section / metering section / die = 170 / 220 / 220 / 220℃ Extrusion temperature of adhesive layer (B): feeding section / compression section / metering section / die = 170 / 220 / 220 / 220°C Extrusion temperature of heat-sealing layer (C): feeding section / compression section / metering section / die = 170 / 220 / 220 / 220℃ Cooling roll temperature: 40℃ Take-off speed: 1.5m / min
[0098] A solution containing a blue dye and a polyurethane binder resin was applied to the substrate layer (Y-1) using a bar coater so that the thickness after drying was 2 μm, and a printed layer was formed by drying for 3 minutes at 80° C. In addition, a two-liquid reactive polyurethane adhesive (24 parts by mass of "Takelac A-520" and 4 parts by mass of "Takenate A-50" manufactured by Mitsui Chemicals, Inc.) was mixed with 37 parts by mass of ethyl acetate to prepare an adhesive solution. Next, the adhesive solution was applied using a bar coater onto the multilayer film (sealant layer (X-1)) obtained above so that the thickness after drying would be 4 μm, and then dried at 80° C. for 3 minutes to form an adhesive layer (Z). This was then laminated with the substrate layer (Y-1) having the printed layer obtained above to produce a multilayer structure having layer thicknesses and layer structure of (Y-1) / printed layer / adhesive layer (Z) / (C) / (B) / (A) / (B) / (C)=50 μm / 2 μm / 4 μm / 60 μm / 4 μm / 6 μm / 4 μm / 60 μm.
[0099] The sealant layer (X-1), the substrate layer (Y-1) and the resulting multilayer structure were evaluated according to the evaluation methods described above. The results are shown in Table 1.
[0100] Examples 2 to 16, Comparative Examples 1 to 5 Multilayer structures were produced and evaluated in the same manner as in Example 1, except that the type of substrate layer (Y), the type of EVOH (a), the thickness of the barrier layer (A), the type of adhesive resin (b), the type of ethylene-α-olefin copolymer resin (c) and the thickness of the adhesive layer (Z) were changed as shown in Table 1. The results are shown in Table 1.
[0101] Comparative Example 6 A multilayer structure was produced and evaluated in the same manner as in Example 1, except that the base layer (Y-1) was not laminated and the sealant layer (X-1) was used as it was as a multilayer structure. The results are shown in Table 1.
[0102] Comparative Example 7 A multilayer structure was produced and evaluated in the same manner as in Example 1, except that a single-layer film of the heat-sealing layer (C) having a thickness of 134 μm was produced and used instead of the multilayer film (sealant layer (X-1)). The results are shown in Table 1.
[0103] [Table 1]
Claims
1. A sealant layer (X) and a substrate layer (Y), The sealant layer (X) comprises a barrier layer (A) containing, as a main component, an ethylene-vinyl alcohol copolymer (a) having an ethylene unit content of 20 to 50 mol% and a saponification degree of 90 mol% or more, an adhesive layer (B) containing, as a main component, an adhesive resin (b), and a cellulose acylate having a density of 0.880 to 0.930 g / cm 3 The thermal adhesive layer (C) contains, as a main component, an ethylene-α-olefin copolymer resin (c) represented by the formula (C), the base layer (Y) contains, as a main component, polypropylene (y) having a melting point of 140° C. or more as measured by a differential scanning calorimeter (DSC), and has an elastic modulus of 1000 MPa or less in both the machine direction and the width direction under conditions of 23° C. and 50% RH; A multilayer structure having a heat-sealing layer (C) of a sealant layer (X) on the outermost surface.
2. Puncture strength S measured according to JIS Z1707:2019 under conditions of 23°C and 50% RH, and puncture strength S of the sealant layer (X) measured according to JIS Z1707:2019 under conditions of 23°C and 50% RH X Difference with (S-S X 2. The multi-layer structure of claim 1, wherein the tension (T) is 3.0 N or greater.
3. 3. The multilayer structure according to claim 2, wherein the puncture strength S is 9N or more.
4. The multilayer structure according to any one of claims 1 to 3, wherein the substrate layer (Y) has a haze of 35% or less as measured in accordance with JIS K 7136:2000.
5. The multilayer structure according to any one of claims 1 to 3, wherein the sealant layer (X) and the base layer (Y) are laminated via the adhesive layer (Z), and the thickness of the adhesive layer (Z) is 2 to 7 µm.
6. The multilayer structure according to any one of claims 1 to 3, wherein the ethylene-α-olefin copolymer resin (c) is a linear low-density polyethylene obtained by copolymerizing ethylene with an α-olefin having 6 or more carbon atoms.
7. 4. The multilayer structure according to claim 1, wherein the barrier layer (A) contains a boron compound in an amount of 50 to 400 ppm calculated as boron element.
8. 4. The multilayer structure according to claim 1, wherein the ethylene unit content of the ethylene-vinyl alcohol copolymer (a) is 22 mol % or more and 28 mol % or less.
9. The multilayer structure according to any one of claims 1 to 3, wherein the barrier layer (A) has a thickness of 5 µm or less.
10. The oxygen transmission rate measured by the method described in JIS K 7126-2:2006 under conditions of 20°C and 65% RH is 5 cc / (m 2 The multilayer structure according to any one of claims 1 to 3, wherein the viscosity is 100 MPa (day·atm) or less.
11. The water vapor transmission rate measured by the method described in JIS K 7129-2:2019 under conditions of 40°C and 90% RH is 3 g / (m 2 The multilayer structure according to any one of claims 1 to 3, wherein the average molecular weight of the polymer is 1000 or less.
12. A packaging material comprising the multilayer structure according to any one of claims 1 to 3.
Citation Information
Patent Citations
Multilayer structure and packaging material comprising same
WO2020071513A1